Pembelajaran Tatap Muka di Tengah Pandemi Covid-19 - Fikri Annur; Ach. Maulidi (Institut Dirosat Islamiyah Al-Amien Prenduan, 2021)
The Covid-19 has affected several educational institutions which decided to implement online learning. But Madrasah Aliyah Nurul Huda was one of the pesantren institutions that carried out face-to-face learning during Covid-19. The purpose of this article was to describe the implementation of face-to-face learning, the impact, the supporting and inhibiting factors of face-to-face learning activities at Madrasah Aliyah Nurul Huda Pekandangan in the midst of Covid-19. This research uses a case study approach in a qualitative method which obtained the primary data from Principal, teachers and students of Madrasah Aliyah Nurul Huda and secondary data from the documentation of Madrasah Aliyah Nurul Huda. Data collection used are interviews, observation and documentation and analyzed them with three interacting analyzes, namely data reduction, data presentation and conclusion. It shows that the Face-to-Face Learning at Madrasah Aliyah Nurul Huda was implemented by reducing the duration of learning which impacted the addition activities outside the classroom and benefited parents that their children were still learning. One of the supporting factor for this implementation is boardng school program, while one of the inhibiting factor is the lack of facilities and infrastructure.